Digital textbooks are useful but not everyone wants them: The role of technostress. (October 2019) - Verkijika, Silas Formunyuy
Abstract: While many theoretical models generally expect a positive relationship between perceived usefulness and the adoption and continuance use of various technologies, the universality of the association has been questionable, suggesting the existence of boundary conditions on the relationship. This study proposes technostress as one such boundary condition and shows that it moderates both the direct and indirect effect of perceived usefulness on the adoption and continuance use of digital textbooks. Two theoretical models (i.e. Adoption model and Continuance use model) were proposed and tested with two samples of students from a South African University. An evaluation of the adoption model showed that the positive direct and indirect effect of perceived usefulness on adoption became non-significant under high levels of technostress. With respect to the continuance use model, it was observed that the direct and indirect effects of perceived usefulness were significant for different levels of technostress; however, the effect was weakest when technostress was high and highest when it was low. Additionally, technostress had a direct negative influence on both the adoption and continuance use of digital textbooks. The findings provide a nuanced understanding of the role of perceived usefulness in the pre and post-adoption phases of digital textbooks. Highlights: The study examines the adoption and continuance use of digital textbooks. Two moderated mediation models are used to evaluate the effect of perceived usefulness. Technostress moderated the direct and indirect effect of perceived usefulness. The effect of usefulness is weakest when technostress is high. Technostress has a negative influence on adoption and continuance intentions.